Theoretical and Methodological Principles of Developing Translational Capabilities of Controlling in Ensuring Sustainable Development of the Enterprise - Tarasova Tetiana O. (Problemi Ekonomiki, 2016)
The aim of the article is to study the role of controlling in modern system of social, ecological, economic relations and assess its capabilities in ensuring sustainable development of a business unit. Under these conditions the concept of controlling should focus on the development of translational capabilities, which provides for the extension of accounting and analytical support functions forming the information environment of the data bank and the knowledge base of management of future events. Taking into account the new management philosophy, it is appropriate to consider controlling as a socio-economic cross-functional management technology, which forms the information space supporting operational, tactical and strategic management by using the mechanism of internal management actions of the reflex nature aimed at sustainable development of the enterprise. There proposed a new direction of the controlling concept based on the philosophy of sustainable development of the enterprise and includes the following translational components: basic and auxiliary business processes; centers of responsibility in the system of business architecture, planning and budgeting systems, motivational tools. In view of the basic management functions the following destination controlling elements are identified: the modeling of the organizational structure of the enterprise as a system of hierarchically dependent business units; formation of a system of operational and strategic planning; development of a tool support system (control values), which allows creating a multilevel system to control achievement of strategic goals and detection of deviations. There proposed a mechanism of forming the information environment of controlling, which includes six interrelated informative components – planning, organizing, monitoring, analysis, regulation consulting, which allows to bridge gaps in information communications in the control system in a single contour of controlling. There presented a model of conceptual environment of controlling in the system of sustainable development management, which serves as the theoretical basis for building the organizational structure of the subdivision of controlling at the enterprise and a methodological basis for accounting and analytical support of management functions and the formalization of the controlling procedures. This made it possible to form the priority objectives of controlling: growth of the enterprise market value; formalization of the evaluation and management of risks; creation of conditions for further development of the controlling system in the information society.